Management Education in teaching and learning a Foreign Language, in particular English language (International Journal of Scientific Research and Management (IJSRM), 2019)
Brain is the most important part of the body in order to achieve goals. It’s important to have clear goals to clarify mind duty and tasks. It’s a difficult life to go on when you have many problems to face, but you can succeed if you make clear intention in what you do. Everything is to face life and find coherence in what you are able to do. Try to make a strategy list to find the right way to give the right time to every point and activity in your life. So you can find the explanation in neuroscience and quantum physic about all phenomena happen around you. Brain areas involve many processes as learning, memorization, in order to achieve better knowledge and skills in getting a foreign language. So brain working is related to neuropsychological research in order to explain process of learning a foreign language. All brain processes are connected with the central nervous system mechanisms that make working all the cerebral mechanisms used. A professional teacher knows how it works in mind process when he teaches a foreign language as English or. French or German or Russian etc